Reducing the cardiovascular disease burden for people of all ages in the Americas region: analysis of mortality data, 2000-15 - Peter Lloyd-Sherlock, ProfPhD; Shah Ebrahim, DM; Ramon Martinez, Eng; Martin McKee, DSc; Pedro Ordunez, PhD (Elsevier, 2019)
Summary: Background: In accordance with the age parameters specified in Sustainable Development Goal target 3.4, current policy and monitoring of non-communicable disease (NCD) mortality trends focus on people aged 30-69 years. This approach excludes the majority of NCD deaths, which occur at older ages. We aimed to compare cardiovascular mortality for different age groups in the WHO Region of the Americas. Methods: We extracted mortality data from the Pan American Health Organization regional mortality database for 36 countries for the period 2000 to 2015. We calculated age-standardised mortality rates (ASMRs) from cardiovascular diseases for different age groups for these countries. Joinpoint regression models were used to estimate mortality trends, providing estimates of the average annual percentage change for the period 2000-15. Findings: Individuals aged 70 years or older accounted for the majority of cardiovascular disease deaths in all countries (range 52-82%). Considerable variation in cardiovascular deaths was observed between countries for all age categories. Between 2000 and 2015, in most countries, the largest reductions in ASMR were observed in the older age groups (aged ≥70 years). The total number of regional cardiovascular disease deaths that hypothetically could have been averted in 2015 for people aged 30-79 years was 440 777, of which 211 365 (48%) occurred among people aged 70-79 years. Interpretation: Data for the WHO Region of the Americas are sufficiently robust to permit comparative analysis of cardiovascular disease mortality trends for people aged 70 years and older over time and across countries. Although the reduction of cardiovascular disease mortality in individuals aged 30-69 years is a valid policy goal for the Americas region, this objective should be expanded to include people at older ages. Funding: None.